2011
DOI: 10.1128/mcb.06092-11
|View full text |Cite
|
Sign up to set email alerts
|

The COMPASS Family of H3K4 Methylases in Drosophila

Abstract: Methylation of histone H3 lysine 4 (H3K4) in Saccharomyces cerevisiae is implemented by Set1/COMPASS, which was originally purified based on the similarity of yeast Set1 to human MLL1 and Drosophila melanogaster Trithorax (Trx). While humans have six COMPASS family members, Drosophila possesses a representative of the three subclasses within COMPASS-like complexes: dSet1 (human SET1A/SET1B), Trx (human MLL1/2), and Trr (human MLL3/4). Here, we report the biochemical purification and molecular characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
230
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(237 citation statements)
references
References 60 publications
6
230
0
1
Order By: Relevance
“…Primary antibodies and dilutions used for staining were: rabbit anti-ASH1 (Novus number 50100002), anti-RNA Pol II Ser2P (Abcam, ab5095), anti-Polycomb (Santa Cruz, number sc-25762), and mouse HGAC-85 anti-O-GlcNAc (Thermo Scientific, number MA1-076). Rabbit anti-SET1 and anti-TRX antibodies were a kind gift from Dr. Shilatifard (38). All secondary antibodies were Alexa Fluor 488-or Alexa Fluor 568-conjugated (Invitrogen) and used at 1/250 dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary antibodies and dilutions used for staining were: rabbit anti-ASH1 (Novus number 50100002), anti-RNA Pol II Ser2P (Abcam, ab5095), anti-Polycomb (Santa Cruz, number sc-25762), and mouse HGAC-85 anti-O-GlcNAc (Thermo Scientific, number MA1-076). Rabbit anti-SET1 and anti-TRX antibodies were a kind gift from Dr. Shilatifard (38). All secondary antibodies were Alexa Fluor 488-or Alexa Fluor 568-conjugated (Invitrogen) and used at 1/250 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…300 g of protein was used for immunoprecipitation in 500 l of PBS, Triton X-100. ASH1 (Novus, number 50100002), BRE1 (Novus, number 40280002), SET1, and TRX antibodies were described (38). All primary antibodies were used at 1/100 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have attributed H3K4me1 to TRR (Ardehali et al 2011;Herz et al 2012), although it has also been assigned to Trithorax (Tie et al 2014). Significantly, CBP and TRR each form a complex containing UTX (Mohan et al 2011;Tie et al 2012), suggesting that these complexes may work in tandem demethylating H3K27 and writing H3K27ac and H3K4me1. To test whether CBP and TRR are involved in intergenic derepression, we knocked each down at 31°C and found that the derepression levels were reduced ( Fig.…”
Section: Global Increase Of H3k27ac and H3k4me1mentioning
confidence: 99%
“…RNAi knockdown experiments show that CBP and TRR contribute to transcriptional derepression but to various extents, depending on the site tested. How H3K27ac and H3K4me1 are mechanistically connected is still not well understood, but both CBP and TRR complexes are reported to include UTX (Mohan et al 2011;Tie et al 2012), which is associated with active transcription (Smith et al 2008). In vitro, mammalian and fly UTX demethylases act preferentially on H3K27me2/3 (Lan et al 2007;Smith et al 2008).…”
Section: Loss Of H3k27 Methylation Causes Global Transcriptional Derementioning
confidence: 99%
“…Mll2 also displayed a high FPKM score (31.451), whereas Mll4, Setd1a, and Setd1b were expressed to much lower degrees, and Mll1 was barely detectable (Supplementary Table S1A). Interestingly, among these six enzymes, only Mll3 and Mll4, both of which are orthologs of Drosophila Trr mediating H3K4me1 at enhancer regions rather than promoter regions [26][27][28], are categorized as "minor ZGA" depending on their expression patterns during the preimplantation stages (Supplementary Table S1A). Because these six methyltransferases are composed of three distinct protein complexes (Supplementary Table S1A) [29], we further examined the expression of molecules unique to each complex.…”
Section: Mll3/4 Expression In the Pn Stage Is Necessary For Early Prementioning
confidence: 99%